Review of acousto-optic spectral systems and applications - Pang, Yajun; Zhang, Kai; Lang, Liying (Frontiers in Physics, 2022)
Acousto-optic devices represented by acousto-optic tunable filters (AOTFs), have the advantages of wide wavelength range from the ultraviolet to the long-wave infrared and fast wavelength switching speed. Nowadays, acousto-optic spectral systems have become very important scientific instruments in laboratory. There are many factors to be considered when we choose different solutions for acousto-optic spectral systems, but there is no comprehensive analysis and summary of them. This paper explains the working principle of the acousto-optic devices and summarizes the most common optical schemes for acousto-optic spectral systems. We also analyzed their characteristics of application conditions. In addition, specific applications of acousto-optic spectral systems in some common fields are presented.